Hubungan Dukungan Sosial Terhadap Derajat Nyeri pada Penderita Artritis Gout Fase Akut - Rofi Rahmaning Widi, Nyoman Kertia, Deddy Nur Wachid (Fakultas Kedokteran Universitas Gadjah Mada, 2011)
The Relationship between Social Support and the Degree ofPain in Patient with Acute Phase of Gout ArthritisBackground: Pharmacological therapies currently used for pain relief in patient with acute phase of gout arthritis often cause serious side effects, such as gastrointestinal bleeding and disturbance of kidney or liver function. The psychological stress is able to increase the pain severity. Some researches conclude that the social support is able to decrease the pain. Other than pharmacological treatment it should be necessary to address the social support in management of patients with acute phase of gout arthritis.Objective: The objective of this research is to determine the extent to which the relationship between social support on the degree of pain in patients with acute phase of gout arthritis.Method: This research used a cross sectional design. There were 21 patients with acute phase of gout arthritis recruited in this research. The questioner of social support and the visual analogue scale were used in this research. Analysis of the relationship of social support and the degree of pain used Pearson correlation.Result: The results of Pearson correlation analysis showed that there was a significant relationship between the social support and the degree of pain (r = - 0.437 and p = 0.047) in patients with acute phase of gout arthritis.Conclusion: This study showed that the higher the social support, the lower the degree of pain in patients with acute phase of gout arthritis.Keywords: social support, degree of pain, acute phase of gout arthritis